Antibacterial Activity Test of Meniran Herb Extract (Phyllanthus Niruri L.) against Staphylococcus Epidermidis and Klebsiella Pneumoniae - Nahrul Hasan Nahrul; Aprilya Sri Rachmayanti; Eem Masaenah (Science Midwifery, 2022)
An antibacterial test of meniran herb extract (Phyllanthus niruri L.) against Staphylococcus epidermidis and Klebsiella pneumoniae has been carried out. Meniran herb powder was screened for phytochemicals to assess the secondary metabolites contained in it, then meniran herbs were extracted using the soxhletation method in stages with various solvents (n-hexane, ethyl acetate, and 70% ethanol). The disc diffusion method was used to test the inhibition zone diameter of n-hexane extract, ethyl acetate extract, and ethanol extract against Staphylococcus epidermidis and Klebsiella pneumoniae. Meniran herb extract was diluted with a concentration series using dimethylsulfoxide. Meniran herb extracts from the three types showed the best inhibition zone diameter when tested for minimum inhibitory concentration (MIC) by the solid dilution method. The results showed that meniran herb powder contained flavonoids, saponins, tannins, glycosides, and steroids/terpenoids. Antibacterial tests showed that ethyl acetate and 70% ethanol extracts had antibacterial activity only against Staphylococcus epidermidis. The antibacterial activity of the two meniran herb extracts had the largest inhibition zone diameter against Staphylococcus epidermidis at a concentration of 50%, which was 12,33 mm for the ethyl acetate extract and 16,00 mm for the ethanol extract. The MIC test of the ethanol extract of the meniran herb, which had the best antibacterial activity, found that at a concentration of 2,5% it was able to inhibit the growth of Staphylococcus epidermidis.